The Influence of the Big Five Personality on the Student’s Motivation in Protecting the Environment - Fitriana, Desi Eka Nur; Miyarsah, Mieke; Rusdi, Rusdi (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
Motivation is a desire or urge contained in a person to act and do something. In this study, motivation focuses on students' motivation in protecting the environment. The existence of motivation is related to a person's personality. This study aims to analyze the direct influence of personality on motivation. This research was conducted using a quantitative approach with survey methods and analyzed using path analysis. The number of samples used as respondents was 200 students in one of the high schools in Tangerang. The results of this study, it can be concluded that there is a positive direct influence of personality on motivation with a path coefficient of 0.581.